2009
DOI: 10.1074/jbc.m109.019315
|View full text |Cite
|
Sign up to set email alerts
|

The Flexible Motif V of Epstein-Barr Virus Deoxyuridine 5′-Triphosphate Pyrophosphatase Is Essential for Catalysis

Abstract: Deoxyuridine 5-triphosphate pyrophosphatases (dUTPases) are ubiquitous enzymes essential for hydrolysis of dUTP, thus preventing its incorporation into DNA. Although Epstein-Barr virus (EBV) dUTPase is monomeric, it has a high degree of similarity with the more frequent trimeric form of the enzyme. In both cases, the active site is composed of five conserved sequence motifs. Structural and functional studies of mutants based on the structure of EBV dUTPase gave new insight into the mechanism of the enzyme. A f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
8
31
0
Order By: Relevance
“…The measured binding affinities and catalytic rates of the T138Stop and H145A enzymes are consistent with the essential role of the C-terminal arm in other dUTPase proteins investigated. 17,25,[27][28][29][30][31][32] To better understand the underlying energetic and structural causes determining the catalytic activity, we carried out QM/MM calculations of the reaction mechanism for proton transfer and phosphate cleavage in the WT and the two mutant (H145A and T138Stop) enzyme complexes. We recently identified a one-step associative A N D N catalytic mechanism for the hydrolysis at the α-phosphate, involving also a coupled proton transfer step from the nucleophilic water to the catalytic Asp83 residue.…”
Section: Introductionmentioning
confidence: 99%
“…The measured binding affinities and catalytic rates of the T138Stop and H145A enzymes are consistent with the essential role of the C-terminal arm in other dUTPase proteins investigated. 17,25,[27][28][29][30][31][32] To better understand the underlying energetic and structural causes determining the catalytic activity, we carried out QM/MM calculations of the reaction mechanism for proton transfer and phosphate cleavage in the WT and the two mutant (H145A and T138Stop) enzyme complexes. We recently identified a one-step associative A N D N catalytic mechanism for the hydrolysis at the α-phosphate, involving also a coupled proton transfer step from the nucleophilic water to the catalytic Asp83 residue.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the active site architecture with bound substrate in the crystal structure of the C-terminally truncated inactive enzyme is identical to that of the wild-type (WT) (7). On the basis of activity measurements on full length and enzymatically truncated Escherichia coli enzymes, it was concluded that ordering of the flexible C terminus upon the active site, which occurs only in the presence of the gamma phosphate (γ-P) containing substrate analog dUPNPP is responsible for dUDP/dUTP discrimination (3,5).…”
mentioning
confidence: 97%
“…The sequence of the C-terminal motif V shares a limited number of features with those of the P-loop motifs (Fig. 1A) (3, 4) present in a large number of ATPase and GTPase enzyme families known as P-loop NTPases including kinases, cytoskeleton and DNA motors, membrane pumps, and transporters.It has been shown that the C terminus of dUTPase is necessary for dUTP hydrolysis but not for nucleotide binding or structural integrity (3,(5)(6)(7). Surprisingly, the active site architecture with bound substrate in the crystal structure of the C-terminally truncated inactive enzyme is identical to that of the wild-type (WT) (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations